2022
DOI: 10.3390/v14122820
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Coronavirus and a Broad Range of Viruses in Kenyan Cave Bats

Abstract: Background and Methods: To investigate virus diversity in hot zones of probable pathogen spillover, 54 oral-fecal swabs were processed from five bat species collected from three cave systems in Kenya, using metagenome sequencing. Results: Viruses belonging to the Astroviridae, Circoviridae, Coronaviridae, Dicistroviridae, Herpesviridae and Retroviridae were detected, with unclassified viruses. Retroviral sequences were prevalent; 74.1% of all samples were positive, with distinct correlations between virus, sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…As this composite genome was elucidated by analyzing interesting MuV-like reads following the conclusion of the collection of environmental swabs and depletion of the original biomaterial, additional attempts to complete the virus genome were not made (i.e., using RT-PCR to fill gaps). This is consistent with similar studies that report the detection of new bat viruses that were characterized as much as possible but were not finished genomes due to sample limitations [ 33 ]. We hypothesize that this newly detected virus, like other bat paramyxoviruses, may persist within individual bats without being consistently shed at detectable titers.…”
Section: Discussionsupporting
confidence: 92%
“…As this composite genome was elucidated by analyzing interesting MuV-like reads following the conclusion of the collection of environmental swabs and depletion of the original biomaterial, additional attempts to complete the virus genome were not made (i.e., using RT-PCR to fill gaps). This is consistent with similar studies that report the detection of new bat viruses that were characterized as much as possible but were not finished genomes due to sample limitations [ 33 ]. We hypothesize that this newly detected virus, like other bat paramyxoviruses, may persist within individual bats without being consistently shed at detectable titers.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to characterize herpesviruses in various host species for better understanding of the evolutionary history and host specificity of herpesviruses. Although partial herpesvirus genes have been detected in bats in various African countries [ 9 , 10 , 11 , 12 , 13 ], Macronycteris vittatus and Hipposideros caffer bats, which live in Africa, had not been analyzed for the detection of herpesviruses. In this study, we carried out the first genetic characterization of herpesviruses from these insectivorous bats living in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…According to the database of zoonotic and vector-borne viruses (ZOVER), 348 complete or partial herpesvirus genomic sequences have been identified in 75 bat species as of 2022 [ 2 ]. In the last two decades, surveillance of herpesvirus infection in bats has been reported in African countries, including Cameroon, the Central African Republic, Ghana, Kenya, Madagascar, the Republic of the Congo, and South Africa [ 9 , 10 , 11 , 12 , 13 ]. In previous studies, herpesviruses were identified in a total of nine bat species in Africa: three species in the family Pteropodidae (frugivorous bats; Eidolon dupreanum , Eidolon helvum , and Rousettus aegyptiacus ), four species in the family Vespertilionidae (insectivorous bats; Miniopterus natalensis , Neoromicia capensis , Neoromicia helios , and Pipistrellus nanulus ), and two species in the family Rhinolophidae (insectivorous bats; Triaenops afer and Triaenops persicus ).…”
Section: Introductionmentioning
confidence: 99%
“…There are however about 180 species of these bats spread across Eurasia and Africa with coronaviruses detected in about 30 of them [19]. Central and South Asia alongside Sub-Saharan Africa are notable absences in Sarbecovirus detection studies [20] with that gap only just beginning to be filled [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%